Who Benefits from Single-Sex Schooling? Evidence on Mental Health, Peer Relationships, and Academic Achievements - Dain Jung; Jun Hyung Kim; Do Won Kwak (Institute of Labor Economics (IZA), 2024)
Single-sex schooling is a controversial policy whose effects are inconsistent across different studies with its mechanisms poorly understood. Leveraging the random allocation of high school students in South Korea, we study the effect of single-sex schooling on mental health while considering its interactions with peer relationships and academic achievement. Our results closely align with gender-specific responses to competitive pressure in the literature. Female students with better academic achievement than their peers experience better mental health and peer relationships. However, relatively underperforming female students, subject to intense competitive pressure at school, do not benefit from being in the company of other female students in a single-sex environment. Impacts on male students do not significantly depend on the competitive pressures they face. Our study calls for caution in implementing educational policies that may affect competitive pressure or gender composition in schools.
Keywords: I21; I24; J16; 330; single-sex schooling; gender and competition; mental health; peer relationship